PENERAPAN METODE DESIGN THINKING DALAM RANCANGAN PROROTYPE WEBSITE DALAM PEMASARAN PARIWITASA DIGITAL - Nurintha Oktaviani (STAH Dharma Sentana Sulawesi Tengah, 2026)
Labuan Bajo is one of the national priority destinations that has unique marine tourism. However, the utilization of digital technology for the promotion of Labuan Bajo is still not optimal. This research aims to design a website prototype that can support the marketing of Labuan Bajo marine tourism using a design thinking approach. The design thinking approach is carried out through five stages: empathize, define, ideate, prototype, and testing. Data was obtained through interviews, distributing questionnaires to 30 respondents, and direct observation. Prototype evaluation was conducted using the System Usability Scale (SUS) method to measure the level of usability and user satisfaction. The results showed that the developed website prototype fulfills user needs, such as complete destination information, intuitive navigation, interactive maps, and online booking features. With an average SUS score of 85.24, the prototype is classified as “Excellent” in terms of usability. Respondents also highly appreciated the visual design and interactive features implemented. This research proves that the design thinking method is effective for developing a digital platform that meets the needs of users. The designed website is expected to support digital marketing strategies, improve information accessibility, and strengthen the attractiveness of Labuan Bajo marine tourism in the global market.